2023
DOI: 10.1111/pbi.14097
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing profiles reveal cell type‐specific transcriptional regulation networks conditioning fungal invasion in maize roots

Abstract: SummaryStalk rot caused by Fusarium verticillioides (Fv) is one of the most destructive diseases in maize production. The defence response of root system to Fv invasion is important for plant growth and development. Dissection of root cell type‐specific response to Fv infection and its underlying transcription regulatory networks will aid in understanding the defence mechanism of maize roots to Fv invasion. Here, we reported the transcriptomes of 29 217 single cells derived from root tips of two maize inbred l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The identification of new direct targets of H 2 O 2 needs to be investigated further. Additionally, single-cell RNA sequencing has been used to study root development in Arabidopsis, maize, and rice [54,[90][91][92][93]. The advancement of new technologies provides new insights into understanding the function of H 2 O 2 in the maintenance of the RAM.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of new direct targets of H 2 O 2 needs to be investigated further. Additionally, single-cell RNA sequencing has been used to study root development in Arabidopsis, maize, and rice [54,[90][91][92][93]. The advancement of new technologies provides new insights into understanding the function of H 2 O 2 in the maintenance of the RAM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the single-cell transcriptome atlas of Arabidopsis leaf vasculature was generated, revealing fundamental differences in amino acid metabolism activity and transport pathways between phloem parenchyma (PP) and CCs (Kim et al 2021 ). Transcriptomic atlas of roots was also reported in rice and maize, which led to the discovery of the unique localization and mobility features of maize SHORT-ROOT (SHR) in the cortex cells (Ortiz-Ramírez et al 2021 ), fungal response mechanisms in maize root tips (Cao et al 2023 ), and cell-type-specific regulatory programs, including phytohormone biosynthesis, signaling, and response, in rice (Liu et al 2021b ; Wang et al 2021 ). Characterization of the single-cell transcriptome of maize shoot apical meristem (SAM) led to the identification of the stem cell cluster, and revealed that genes involved in DNA damage repair, methylation, and genome stability maintenance are significantly upregulated in stem cells, providing insights into stem cell function and fate acquisition (Satterlee et al 2020 ).…”
Section: Application Areas Of Single-cell Multi-omics Approaches In P...mentioning
confidence: 99%
“…The signaling pathways that plants use to adapt to environmental changes and pathogen infection have also been identified at a high resolution. Six immune regulatory networks controlling Fusarium verticillioides ( Fv ) pathogenesis in the major cell types of maize root tips at single-cell resolution were constructed (Cao et al 2023 ). Exposing Arabidopsis to Pseudomonas syringae and profiling > 11,000 individual cells using scRNA-seq led to the identification of distinct pathogen-responsive cell clusters exhibiting transcriptional responses ranging from immunity to susceptibility, which resolved the cellular heterogeneity within an infected leaf (Zhu et al 2023b ).…”
Section: Application Areas Of Single-cell Multi-omics Approaches In P...mentioning
confidence: 99%
“…In recent years, signi cant breakthroughs have been achieved in the eld of plant research using singlecell transcriptomic (scRNA-seq) technology, which is a powerful tool to study the processes underlying plant growth and development, with A. thaliana emerging as a pivotal subject of investigation, with analyses focusing on various tissue types such as roots, stems, and leaves [13,[20][21][22][23][24][25]. Additionally, attention has been directed to other plants including the cabbage [26,27], maize [28][29][30][31], rice [32][33][34].…”
Section: Introductionmentioning
confidence: 99%